Arboricoltura di precisione: un nuovo approccio alla gestione del rischio caduta alberi basato sulla Geomatica - Samuele De Petris (mediaGEO soc. coop., 2021)
Trees provide social, economic and aesthetic benefits to human beings but often they present structural defects,physiological disorders and/or pathological processes that pose a danger to property and people. In this work we applied Precision Arboriculture approach at La Mandria regional park (Piedmont). UAV digital photogrammetry was used to retrieve tree parameters in a jointly use to multispectral satellite remote sensing (Copernicus Sentinel- 2) to monitor the canopy health of trees. The adoption of biomechanical models has made it possible to assess the mechanical stability of the trunks and create a decision support system that creates intervention priorities zones with the aim of reducing and optimizing ground tree inspections.